Cylindrical lithium primary battery
Patent Information
- Application Number
- JP2025062718
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
Smart Images

Figure 2026169055000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a cylindrical lithium primary battery with excellent storage characteristics. [Background technology]
[0002] Cylindrical lithium primary batteries, which are constructed by stacking a negative electrode and a positive electrode, both using lithium as the active material, with a separator in between, and then winding them to form a spiral electrode body, are inserted into an outer casing and sealed. Compared to batteries with alkaline electrolytes, for example, they have a higher energy density and can be used for long periods of time, and are therefore used in a variety of applications.
[0003] While cylindrical lithium primary batteries were known for applications such as light loads like memory backup and heavy loads like those in cameras, the diversification of application devices has led to an increase in medium-load applications such as data transmission and reception. Therefore, there is a demand for the development of batteries that can achieve high capacity under medium loads. Furthermore, cylindrical lithium primary batteries also require long-term reliability.
[0004] For example, Patent Document 1 proposes a technology for cylindrical non-aqueous electrolyte primary batteries, such as cylindrical lithium primary batteries, in which the thickness of the positive electrode is 1.4 mm or more, and two independent films made of resin with a thickness of 7 to 20 μm are used as separators interposed between the positive and negative electrodes, and these films are stacked without being bonded to each other, thereby enabling high capacity and ensuring long-term reliability.
[0005] Furthermore, Patent Document 2 proposes a technology that enables the provision of lithium primary batteries with excellent discharge capacity and self-discharge rate by using a non-aqueous electrolyte containing a nitrile compound and an S=O group-containing compound. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] International Publication No. 2020 / 054662 [Patent Document 2] Japanese Patent Publication No. 2004-179146 [Overview of the project] [Problems that the invention aims to solve]
[0007] Incidentally, cylindrical lithium primary batteries are also required to have improved storage characteristics, for example, depending on their application, and even the batteries described in the aforementioned literature still have room for improvement in this regard.
[0008] This invention has been made in view of the above circumstances, and its purpose is to provide a cylindrical lithium primary battery with excellent storage characteristics. [Means for solving the problem]
[0009] The cylindrical lithium primary battery of the present invention comprises an electrode body formed by spirally winding a positive electrode and a negative electrode with a separator in between, and an electrolyte sealed within an outer casing. The positive electrode includes a positive electrode current collector and positive electrode mixture layers arranged on both sides of the positive electrode current collector, each containing manganese dioxide as the positive electrode active material. The manganese dioxide content per unit area of the positive electrode mixture layer is 0.155 to 0.185 g / cm³ per side of the positive electrode current collector. 2 The negative electrode comprises a negative electrode current collector and a lithium layer laminated on one side of the negative electrode current collector, wherein the lithium layer has a lithium-aluminum alloy formed on the separator side surface, the ratio of the total amount of aluminum to the total amount of lithium in the entire lithium layer is 0.15 to 0.36 by mass ratio, and the electrolyte contains dinitrile. [Effects of the Invention]
[0010] According to the present invention, a cylindrical lithium primary battery with excellent storage characteristics can be provided. [Brief explanation of the drawing]
[0011] [Figure 1] FIG. 2 is a vertical cross-sectional view schematically showing an example of the cylindrical lithium primary battery of the present invention. [Figure 2] FIG. 2 is a transverse cross-sectional view of the cylindrical lithium primary battery in FIG. 1. [Figure 3] FIG. 3 is a partial cross-sectional view schematically showing an example of an electrode assembly with a wound structure that constitutes the cylindrical lithium primary battery. [Figure 4] FIG. 4 is a partial cross-sectional view schematically showing an example of a laminate in which a negative electrode current collector, two lithium layers and a separator are integrated, which is used when producing the electrode assembly with a wound structure constituting the cylindrical lithium primary battery. [Figure 5] FIG. 5 is a diagram for explaining a method for producing the electrode assembly with a wound structure constituting the cylindrical lithium primary battery. [Figure 6] FIG. 6 is a diagram for explaining a method for producing the electrode assembly with a wound structure constituting the cylindrical lithium primary battery. [Figure 7] FIG. 7 is a graph showing the storage characteristic evaluation results of the cylindrical lithium primary batteries of Example 1 and Comparative Example 1. [Mode for Carrying Out the Invention]
[0012] The cylindrical lithium primary battery of the present invention is configured by enclosing an electrode assembly of a wound structure, which is formed by spirally winding a positive electrode and a negative electrode with a separator interposed therebetween, and an electrolytic solution in an outer can. In the present invention, the positive electrode mixture layer of the positive electrode contains a large amount of manganese dioxide which is the positive electrode active material, and this enables, for example, an increase in capacity.
[0013] Further, in the cylindrical lithium primary battery of the present invention, a lithium-aluminum alloy is formed on the surface of the lithium layer of the negative electrode, and the ratio of the total amount of aluminum to the total amount of lithium in the entire lithium layer is set to a specific value, thereby increasing the reaction area on the negative electrode surface, which enables, for example, improvement of load characteristics.
[0014] Furthermore, the cylindrical lithium primary battery of the present invention has an electrolyte containing dinitrile.
[0015] In batteries using manganese dioxide as the positive electrode active material, there is a problem of increased resistance due to manganese dissolving into the electrolyte and depositing on the negative electrode surface. This problem tends to become more pronounced, for example, when the battery is stored at high temperatures. However, the dinitrile contained in the electrolyte forms a film on the positive electrode surface, which has the effect of suppressing the increase in resistance. Therefore, in the cylindrical lithium primary battery of the present invention, it is possible to suppress the increase in impedance even after storage at high temperatures of, for example, around 80°C, thereby ensuring excellent storage characteristics.
[0016] First, the structure of a cylindrical lithium primary battery will be explained using drawings. Figures 1 and 2 are schematic diagrams illustrating an example of a cylindrical lithium primary battery. Figure 1 is a longitudinal cross-sectional view of the cylindrical lithium primary battery, and Figure 2 is a transverse cross-sectional view of the cylindrical lithium primary battery of Figure 1. Note that the longitudinal cross-section of the cylindrical lithium primary battery 1 shown in Figure 1 corresponds to the cross-section of line II in Figure 2. Figure 3 is a schematic partial cross-sectional view illustrating an example of a wound electrode structure constituting a cylindrical lithium primary battery.
[0017] The cylindrical lithium primary battery 1 comprises a bottomed cylindrical outer casing 2 with an upper opening, an electrode body (winding structure electrode body) 3 formed by spirally winding a positive electrode 4 and a negative electrode 5 loaded inside the outer casing 2 via a separator 6, an electrolyte, and a sealing body that seals the upper opening of the outer casing 2. In other words, the cylindrical lithium primary battery 1 shown in Figure 1 has power generation elements such as a winding structure electrode body 3, formed by spirally winding a positive electrode 4 and a negative electrode 5 via a separator 6, and an electrolyte, within the space surrounded by the outer casing 2 and the sealing body that seals the upper opening of the outer casing 2.
[0018] As shown in Figure 2, the wound electrode body 3 is formed by winding a long positive electrode 4 and a long negative electrode 5 with a separator 6 in between, and is formed in a substantially cylindrical shape overall. As shown in Figures 2 and 3, the positive electrode 4 has a structure in which two positive electrode mixture sheets (positive electrode mixture layers) 41 and 42 are stacked on a positive electrode current collector 43. That is, the positive electrode 4 has a structure in which the two positive electrode mixture sheets have positive electrode mixture layers 41 and 42 on both sides of the positive electrode current collector 43.
[0019] Furthermore, as shown in Figures 2 and 3, the negative electrode 5 has a structure in which a lithium layer 51 is laminated on one side of the current collector 52. In the wound electrode body 3, as shown in Figure 2, a single long negative electrode 5 is wound by folding it back at the winding center. Therefore, in the cross-section shown in Figure 1, the negative electrodes 5 are in contact with each other on the current collector side, and the lithium layer 51 of each negative electrode 5 faces the positive electrode 4 via the separator 6.
[0020] In Figures 1 and 2, the separator 6 is shown as a single layer; however, in a cylindrical lithium primary battery, one single layer separator may be used, or a multi-layer separator may be used, such as the separator 6 with two layers 61 and 62 shown in Figure 3.
[0021] The sealing body of the cylindrical lithium primary battery 1, as shown in Figure 1, may have a cover plate 7 fixed to the inner periphery of the upper opening of the outer casing 2, a terminal body 9 mounted via an insulating packing 8 made of polypropylene or the like in an opening in the center of the cover plate 7, and an insulating plate 10 positioned below the cover plate 7. The insulating plate 10 is formed in the shape of a round plate opening upward, with an annular side wall 12 erected on the periphery of a disc-shaped base portion 11, and a gas vent 13 is provided in the center of the base portion 11. The cover plate 7 is fixed to the inner periphery of the upper opening of the outer casing 2 by laser welding or by a crimp seal via packing, while being supported by the upper end of the side wall 12. As a countermeasure when the internal pressure of the battery rises rapidly, a thin-walled portion (vent) can be provided in the cover plate 7 or the bottom 2a of the outer casing 2. The positive electrode 4 and the lower surface of the terminal body 9 are connected by a positive electrode lead body 15. Furthermore, the negative electrode lead body 16 attached to the negative electrode 5 is welded to the upper inner surface of the outer casing 2. In addition, a resin insulating plate 14 is placed at the bottom 2a of the outer casing 2.
[0022] In Figure 1, the terminal body 9 does not have hatching to show a cross-section in order to make the drawing easier to read. Note that the positive lead body 15 and the negative lead body 16 are located outside the cross-sectional area shown in Figure 1, and therefore do not originally show a cross-section.
[0023] Next, we will describe the details of each component of a cylindrical lithium primary battery.
[0024] (positive electrode) The positive electrode of a cylindrical lithium primary battery comprises a positive electrode current collector and a positive electrode mixture layer arranged on both sides of the positive electrode current collector.
[0025] The positive electrode mixture layer contains manganese dioxide as the positive electrode active material. In addition to the positive electrode active material, the positive electrode mixture layer usually contains a conductive additive and a binder. Examples of conductive additives include graphite, carbon black (such as Ketjenblack®, acetylene black, and furnace black), and one of these may be used alone or two or more may be used in combination. As for the binder, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), and rubber-based binders can be used. In the case of fluororesins such as PTFE and PVDF, they may be in dispersion type or powder form, but the dispersion type is particularly preferred.
[0026] In the positive electrode mixture layer, for example, the content of the positive electrode active material is preferably 92 to 97% by mass, the content of the conductive additive is preferably 2 to 3.5% by mass, and the content of the binder is preferably 1 to 4.5% by mass.
[0027] In the positive electrode, the manganese dioxide content per unit area of the positive electrode mixture layer is 0.155 to 0.185 g / cm³. 2 That is, the positive electrode has manganese dioxide content of 0.155 to 0.185 g / cm³ per unit area on both sides of the positive electrode current collector. 2 Each positive electrode has a positive electrode mixture layer that has been adjusted accordingly. The manganese dioxide content per unit area in the positive electrode mixture layer is 0.155 g / cm³ per side of the positive electrode current collector. 2 By doing so, the electrode capacity can be increased even if the length of the positive electrode is relatively short. Therefore, the length (volume) of the separator can be reduced and the proportion of active materials in the positive and negative electrodes can be increased, making it easier to design high-capacity batteries. On the other hand, the manganese dioxide content in the positive electrode mixture layer is set to 0.185 g / cm³ per side of the positive electrode current collector. 2In order to make it larger, it is necessary to lower the porosity of the positive electrode mixture layer more than necessary, or make the positive electrode mixture layer thicker than necessary, so that the number of windings of the positive electrode is less than 2.5. In the former case, the permeability of the electrolytic solution into the positive electrode mixture layer decreases, and the reactivity of the positive electrode decreases, so the load characteristics of the battery deteriorate. Also in the latter case, the reaction area of the electrode decreases, so the load characteristics of the battery deteriorate. Therefore, the content of manganese dioxide per unit area contained in the positive electrode mixture layer is set to 0.185 g / cm per one side of the positive electrode current collector 2 By setting it to the following range, it is possible to achieve higher capacity of the battery and enhance the load characteristics of the battery.
[0028] The density of the positive electrode mixture layer is 2.4 g / cm for the purpose of increasing the capacity of the battery 3 It is preferably set to the above value, and 2.45 g / cm 3 It is more preferably set to the above value, and 2.5 g / cm 3 It is even more preferably set to the above value. On the other hand, in order to improve the permeability of the non-aqueous electrolytic solution and prevent the deterioration of discharge characteristics, the density of the positive electrode mixture layer is 2.7 g / cm 3 It is preferably set to the following range, and 2.65 g / cm 3 It is more preferably set to the following range, and 2.6 g / cm 3 It is even more preferably set to the following range.
[0029] Examples of the current collector used for the positive electrode include those made of stainless steel such as SUS316, SUS430, and SUS444, and aluminum, and examples of the form thereof include plain woven wire mesh, expanded metal, lath mesh, punching metal, foil (plate), and the like. The thickness of the positive electrode current collector is preferably 0.1 to 0.4 mm.
[0030] The thickness of the positive electrode is, for example, 1.3 mm or more, preferably 1.4 mm or more, more preferably 1.45 mm or more, preferably 1.8 mm or less to maintain flexibility, more preferably 1.7 mm or less, and particularly preferably 1.6 mm or less. Furthermore, the thickness of the positive electrode mixture layer can be set, for example, within a range where the sum of the thicknesses of the positive electrode mixture layers arranged on both sides of the positive electrode current collector satisfies the aforementioned total thickness of the positive electrode and the aforementioned thickness of the positive electrode current collector.
[0031] The positive electrode can be manufactured, for example, by mixing a positive electrode active material with a conductive additive and a binder, and adding water as needed to create a positive electrode mixture (slurry), which is then rolled using a roll or the like to form a pre-sheet, which is then dried and pulverized and again roll-rolled to form a sheet shape to create a positive electrode mixture sheet, which is then placed on both sides of the current collector, and the positive electrode mixture sheet and the current collector are integrated by pressing or the like to form a layer (positive electrode mixture layer) consisting of the positive electrode mixture sheet on both sides of the current collector.
[0032] A positive electrode having positive electrode mixture layers on both sides of the current collector can be manufactured, for example, by overlapping the three components such that the outer circumference of the current collector is several millimeters inward from the outer circumferences of the two positive electrode mixture sheets, and then pressing a portion 3 to 10 mm from the longitudinal end that is positioned on the winding core side during winding.
[0033] Furthermore, the positive electrode is not limited to those manufactured by the above-described method, but may be manufactured by other methods. For example, a positive electrode manufactured by a method in which a positive electrode mixture slurry is applied to both sides of a current collector, dried, and then pressed or otherwise subjected to other processes as necessary to form a positive electrode mixture layer on the current collector may also be used.
[0034] A paste-like conductive material can be applied to the surface of the positive electrode current collector. Even when a mesh-like positive electrode current collector with a three-dimensional structure is used, a significant improvement in current collection efficiency can be observed by applying a conductive material, similar to when using materials that are essentially flat plates, such as metal foil or perforated metal. This is presumed to be because the current is effectively utilized not only through the direct contact path between the metal parts of the mesh current collector and the positive electrode mixture layer, but also through the conductive material filled within the mesh.
[0035] For example, silver paste or carbon paste can be used as the conductive material. As the binder for the conductive material, it is preferable to use a heat-resistant material such as water glass or imide-based binder, as this allows for drying at high temperatures exceeding 200°C to remove moisture from the positive electrode mixture layer.
[0036] (Negative electrode) The negative electrode of a cylindrical lithium primary battery comprises a negative electrode current collector and a lithium layer laminated on one side of the negative electrode current collector. The lithium layer can be made of metallic lithium foil (including lithium alloy foil).
[0037] The negative electrode current collector can be made of foil made of copper, nickel, iron, stainless steel, or the like. The thickness of the negative electrode current collector is preferably as thin as possible; specifically, it is recommended to be, for example, 25 μm or less. On the other hand, if the negative electrode current collector is too thin, it becomes easily torn, so the thickness of the negative electrode current collector is preferably 5 μm or more. Furthermore, the width of the negative electrode current collector is preferably the same as or wider than the width of the lithium layer. Also, the area of the negative electrode current collector is preferably 100% or more of the area of the lithium layer. By setting the area of the negative electrode current collector as described above, the width and length of the negative electrode current collector become the same as or greater than the width and length of the lithium layer, thus preventing the electrical connection from being broken even if a crack occurs in the metallic lithium foil during discharge.
[0038] On the other hand, as the proportion of areas on the negative electrode current collector where the lithium layer is not laminated increases, there is a risk that the effect of increasing the battery capacity will decrease. Therefore, it is preferable that the area of the negative electrode current collector be 120% or less of the area of the lithium layer. In other words, it is preferable that the area of the lithium layer laminated on the negative electrode current collector be 83% or more of the area of the negative electrode current collector.
[0039] In the negative electrode, the surface of the lithium layer located on the separator side is alloyed with aluminum. That is, a lithium-aluminum alloy is formed on the separator-side surface of the lithium layer in the negative electrode. This makes it possible to further improve the battery's load characteristics.
[0040] On the separator-side surface of the lithium layer, it is preferable that a lithium-aluminum alloy is formed over 90% or more of the total surface area of the lithium layer, from the viewpoint of further enhancing the effect of improving the load characteristics of the battery.
[0041] Furthermore, from the viewpoint of improving the load characteristics of the battery, in the negative electrode, the ratio of the total amount of aluminum (the total mass of aluminum in the lithium-aluminum alloy; the same applies hereinafter) to the total amount of lithium in the entire lithium layer (the total mass of lithium in the lithium-aluminum alloy and lithium that is not alloyed; the same applies hereinafter) is preferably 0.15 or more, more preferably 0.2 or more, and more preferably 0.25 or more, in terms of mass ratio. On the other hand, as the proportion of aluminum increases, the discharge capacity of the negative electrode decreases, which may reduce the effect of increasing the battery's capacity. Therefore, the ratio of the total amount of aluminum to the total amount of lithium in the entire lithium layer of the negative electrode is preferably 0.36 or less, more preferably 0.33 or less, and more preferably 0.3 or less, in terms of mass ratio.
[0042] By creating a negative electrode by laminating aluminum foil on top of a metallic lithium foil, and then assembling a battery using this negative electrode, a lithium-aluminum alloy can be formed on the surface of the lithium layer within the battery.
[0043] When forming a lithium-aluminum alloy on the surface of a lithium layer within a battery, the thickness of the metallic lithium foil used to fabricate the negative electrode is, for example, 0.18 to 0.25 mm, and the thickness of the aluminum foil is, for example, 7 to 15 μm.
[0044] In cylindrical lithium primary batteries, the positive electrode has increased capacity by increasing the manganese dioxide content in the positive electrode mixture layer, and it is desirable to increase the capacity of the negative electrode accordingly. Specifically, the lithium layer that forms the active material layer of the negative electrode should have a lithium content of 0.01 to 0.014 g / cm³ per unit area. 2 It is preferable to adjust it to this.
[0045] Furthermore, in order to maintain a constant ratio between the capacity of the positive electrode and the capacity of the negative electrode, the ratio of the lithium content per unit area of the lithium layer to the manganese dioxide content per unit area of the positive electrode mixture layer (per one side of the positive electrode current collector) (the ratio of the lithium content when the manganese dioxide content is set to 1) is preferably 0.067 to 0.08 by mass ratio.
[0046] The lithium layer in the negative electrode may be continuous throughout, but it is preferable that it is divided into two at the center 18 of the winding structure of the electrode body 3, as shown in Figure 2. In this case, the divided lithium layer faces one of the positive electrode mixture layers located on both sides of the positive electrode current collector.
[0047] In the electrode body 3 of the cylindrical lithium primary battery 1 shown in Figure 2, the long negative electrode 5 is folded back between two lithium layers 51, 51, and at a position close to one of the lithium layers (the lithium layer facing the positive electrode mixture layer 42 on the inner surface side of the positive electrode 4), for example, at a position of approximately 1 mm from the inner circumference end (the end on the winding start side) of the lithium layer, so as to be roughly aligned with the winding core that was removed after winding. The negative electrode current collectors overlap each other, and the inner circumference ends of the two lithium layers 51, 51 are each located outside the winding center 18. One of these lithium layers 51, 51 faces the positive electrode mixture layer 41 located on one side of the positive electrode current collector 43, and the other faces the positive electrode mixture layer 42 located on the other side of the positive electrode current collector 43.
[0048] Here, the winding center 18 refers to the portion of the negative electrode that is sandwiched between winding cores (for example, width: approximately 3 mm) during winding, and its length is approximately the same as the width of the winding core. As a result, the thickness of the negative electrode sandwiched between the winding cores becomes thinner compared to when the lithium layer is formed as a single continuous body, thus reducing the winding diameter of the wound electrode body. Furthermore, because the two lithium layers 51, 51 are spaced apart in the longitudinal direction, in the inner negative electrode current collector of the stacked negative electrode current collectors 52, a portion of a certain width or more in which the lithium layer is not stacked can be formed from the winding center toward the positive electrode mixture layer 41 on the outer surface of the positive electrode 4.
[0049] The width of the portion where the lithium layer is not laminated can be appropriately adjusted by the length from the center of the winding to the outer positive electrode mixture layer 41, but it is preferably 2 mm or more from the center of the winding, and more preferably 4 mm or more.
[0050] Furthermore, it is preferable that the two lithium layers 51, 51 are arranged on the negative electrode current collector 52 with a gap of 6 mm to 12 mm in the longitudinal direction. In this case, there will be a region between the two lithium layers 51, 51 where a lithium layer is not formed and the negative electrode current collector 52 is exposed, with a width of 6 mm to 12 mm in the longitudinal direction (winding direction).
[0051] In the negative electrode current collector on the inner side, the portion between the winding center 18 and the beginning end of the positive electrode mixture layer 41 of the positive electrode 4 does not face the positive electrode 4. Therefore, by not laminating a lithium layer on the negative electrode current collector in this portion, the amount of lithium not involved in discharge can be reduced, and the discharge efficiency can be improved. Furthermore, as described above, by making the thickness of the beginning portion of the negative electrode 5 thinner, the winding diameter of the wound electrode body 3 can be made smaller. From these viewpoints, it is more preferable that the distance between the two lithium layers 51, 51 be 8 mm or more.
[0052] Furthermore, if the distance between the two lithium layers 51, 51 becomes too wide, the starting portion of the positive electrode mixture layer will no longer face the lithium layer, which may reduce the effect of increasing capacity. To prevent the above problem, the distance between the two lithium layers 51, 51 is preferably 12 mm or less, and more preferably 10 mm or less.
[0053] (Separator) The separator for cylindrical lithium primary batteries uses materials such as microporous films or nonwoven fabrics made of resin. Examples of resins used for the separator include polyolefins such as polyethylene (PE) and polypropylene (PP); polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT); and polyphenylene sulfide (PPS). One or more of these materials can be used.
[0054] The thickness of the separator is preferably 7 μm or more, more preferably 10 μm or more, preferably 20 μm or less, and more preferably 18 μm or less, in the case of a microporous film. In the case of a nonwoven fabric, the thickness is preferably 10 μm or more, more preferably 20 μm or more, preferably 80 μm or less, and more preferably 50 μm or less.
[0055] As mentioned above, a single-layer separator may be used, but as the battery capacity increases, the risk of short circuits also tends to increase. Therefore, as shown in Figure 3, it is preferable to use a multi-layer separator. A multi-layer separator can be constructed, for example, by layering two microporous resin films, or by layering one microporous resin film and one nonwoven fabric.
[0056] (electrolyte) The electrolyte for cylindrical lithium primary batteries is a solution (non-aqueous electrolyte) in which lithium salts such as LiClO4, LiCF3SO3, LiC2F5SO3, LiN(FSO2)2, and LiN(CF3SO2)2 are dissolved in an organic solvent.
[0057] Examples of organic solvents include cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and vinylene carbonate; linear carbonates such as dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate; ethers such as 1,2-dimethoxyethane (ethylene glycol dimethyl ether), diglyme (diethylene glycol dimethyl ether), triglyme (triethylene glycol dimethyl ether), tetraglyme (tetraethylene glycol dimethyl ether), methoxyethoxyethane, 1,2-diethoxyethane, and tetrahydrofuran; cyclic esters such as γ-butyrolactone; and nitriles. Only one of these may be used, or two or more may be used in combination. In particular, it is preferable to use the above-mentioned cyclic carbonate and ether in combination.
[0058] As the cyclic carbonate, ethylene carbonate and propylene carbonate are preferably used. As the ether, 1,2-dimethoxyethane is preferably used. From the viewpoint of ensuring good lithium ion conductivity, the concentration of the lithium salt in the non-aqueous electrolyte is preferably 0.3 mol / L or higher, more preferably 0.4 mol / L or higher, preferably 1.2 mol / L or lower, and more preferably 1.0 mol / L or lower.
[0059] The electrolyte contains dinitrile. This allows a film to form on the surface of the positive electrode, which suppresses the leaching of manganese from the positive electrode and prevents the increase in resistance caused by its deposition on the negative electrode surface. Therefore, the cylindrical lithium primary battery of the present invention can improve its storage characteristics.
[0060] Specific examples of dinitriles include malononitrile, succinonitrile, glutalonitrile, adiponitrile, 1,4-dicyanoheptane, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 2,6-dicyanoheptane, 1,8-dicyanooctane, 2,7-dicyanooctane, 1,9-dicyanononane, 2,8-dicyanononane, 1,10-dicyanodecane, 1,6-dicyanodecane, and 2,4-dimethylglutalonitrile. One or more of these can be used. Among these, succinonitrile or adiponitrile is preferred because they are highly effective in suppressing metal elution in high-temperature environments.
[0061] The dinitrile content in the electrolyte used for cylindrical lithium primary batteries is preferably 0.5% by mass or more, and more preferably 1% by mass or more, from the viewpoint of better ensuring the effects of using dinitrile. However, if the amount of dinitrile in the electrolyte is too high, the film formed on the positive electrode surface will become too thick, making it difficult to reduce the internal resistance, and the effects of using dinitrile may be diminished. Therefore, the dinitrile content in the electrolyte used for cylindrical lithium primary batteries is preferably 5% by mass or less, and more preferably 4% by mass or less.
[0062] Furthermore, the amount of electrolyte contained in a cylindrical lithium primary battery is preferably 0.365 or higher, and more preferably 0.375 or higher, as a ratio (mass ratio) of the total amount of electrolyte to the total amount of manganese dioxide in the positive electrode mixture layer. This allows manganese dioxide to contribute well to the discharge reaction throughout the entire positive electrode mixture layer, thereby further improving the battery's capacity.
[0063] However, if the amount of electrolyte introduced into a cylindrical lithium primary battery is too large, there is a risk that some of the electrolyte may leak out and adhere to the outside of the outer casing during sealing, thus impairing the sealing performance. Therefore, from the viewpoint of further improving the reliability and productivity of the battery, the ratio of the total amount of electrolyte to the total amount of manganese dioxide in the positive electrode mixture layer is preferably 0.4 or less, and more preferably 0.39 or less.
[0064] (Outer can) The outer casing of a cylindrical lithium primary battery can be made of iron, stainless steel, or other materials. Examples of stainless steel include austenitic stainless steels such as SUS301, SUS304, and SUS316 (as specified by the Japanese Industrial Standards (JIS)); austenitic-ferritic stainless steels such as SUS329J1, SUS329J3L, and SUS329J4L; and ferritic stainless steels such as SUS430 and SUS444. The outer casing can also be made of cold-rolled steel sheet (such as SPCD, SPCE, or SPCF). The surface of the outer casing may be coated with an anti-corrosion plating, such as nickel plating.
[0065] The outer casing preferably has a side thickness of 0.26 mm or less, and more preferably 0.255 mm or less. By using an outer casing with a thin side thickness and a large internal volume as described above, the decrease in the insertability of the wound electrode body into the outer casing can be suppressed more effectively, thereby further suppressing the decrease in battery reliability and productivity.
[0066] However, if the sides of the outer casing are too thin, the strength of the casing may be reduced too much. Therefore, from the viewpoint of maintaining sufficient strength so as not to cause problems with the use of the battery, the thickness of the sides of the outer casing is preferably 0.24 mm or more, and more preferably 0.245 mm or more.
[0067] (Electrode body with a wound structure, and method for manufacturing the same) In the wound electrode structure of a cylindrical lithium primary battery, it is preferable that the number of turns of the positive electrode is 2.5 to 3.5. This increases the surface area between the positive and negative electrodes in the electrode body, i.e., the reaction area, thereby improving the load characteristics of the battery.
[0068] In this specification, the number of turns of the positive electrode refers to the number of turns in the positive electrode mixture layer from one end (one of the longitudinal ends) to the other end (the other longitudinal end) of the positive electrode mixture layer. For example, the number of turns of the positive electrode in the electrode body shown in Figure 2 is approximately 2.5.
[0069] The wound electrode body for a cylindrical lithium primary battery can be manufactured, for example, by the procedure shown in Figures 4, 5, and 6. In Figures 4, 5, and 6, the separator 6 is shown as a single-layer structure. Here, the procedure for manufacturing a wound electrode body having a negative electrode with a structure in which the lithium layer is divided into two parts with the winding center in between will be explained as an example.
[0070] First, as shown in Figure 4, the separator 6 is fixed to the negative electrode current collector 52 by placing adhesive tape 31 and the separator 6 on the upper surface of the central part in the longitudinal direction of the negative electrode current collector 52. Double-sided tape can be used for the adhesive tape 31. Next, two lithium layers 51, 51 are pressed and fixed to both sides in the longitudinal direction of the negative electrode current collector 52, sandwiching the fixed portion of the separator 6. In other words, a portion is provided on one side of the negative electrode current collector 52 where the lithium layer, which is the negative electrode active material, is not formed and the negative electrode current collector 52 is exposed, and the separator 6 is fixed to this exposed portion 30 with adhesive tape 31. At this time, the width of the exposed portion 30 (the distance between the two lithium layers 51, 51 in the longitudinal direction) is preferably 6 mm or more and 12 mm or less, as described above. In this way, a laminate 32 in which the negative electrode current collector 52, the two lithium layers 51, 51, and the separator 6 are integrated can be obtained.
[0071] Furthermore, when forming the lithium-aluminum alloy on the surface of the lithium layer within the battery, the laminate can be constructed by further laminating aluminum foil 51b on top of metallic lithium foil 51a, as shown in the enlarged view in Figure 4. That is, the lithium layer 51 shown as a single-layer structure in Figures 4, 5, and 6 can be a laminate of metallic lithium foil 51a and aluminum foil 51b, as shown in the enlarged view in Figure 4. On the other hand, when assembling a battery using a negative electrode that already has a lithium-aluminum alloy on the surface of the lithium layer, the lithium-aluminum alloy is formed on the surface of the lithium layer 51 shown as a single-layer structure in Figures 4, 5, and 6 (i.e., this lithium layer 51 uses metallic lithium foil with a lithium-aluminum alloy formed on one side of its surface).
[0072] Next, as shown in Figure 5, the laminate 32 is inserted between the lateral grooves 33a of the winding core 33. The width of the lateral grooves 33a of the winding core 33 is, for example, 2.8 mm. In this case, the distance between the left end of the lateral groove 33a of the winding core 33 and the end of the lithium layer 51 in Figure 5 is approximately 1 mm, and the exposed portion 30, that is, the portion of the separator 6 fixed by the adhesive tape 31, is positioned so that it is between the lateral grooves 33a of the winding core 33.
[0073] In the state described above, the winding core 33 is rotated about half a turn in one direction (clockwise in Figure 5) to wind the laminate 32 around the outer surface of the winding core 33 as shown in Figure 6. Next, the positive electrode 4, consisting of positive electrode mixture sheets 41, 42 and a positive electrode current collector 43, is placed on the separator 6 and wound together with the laminate 32 on the winding core 33. After winding the laminate 32 and the positive electrode 4, the winding core 33 is removed from the winding body, and finally the winding end of the lithium layer 51 is fixed with fixing tape. Here, the negative electrode 5 is folded back between the two lithium layers 51, 51, at a position of about 1 mm from one of the lithium layers 51, and the negative electrode current collectors 52 overlap each other, and the inner ends of the two lithium layers 51, 51 are each located outside the winding center 18. The folding position of the negative electrode is preferably, for example, within 1.5 mm from one of the lithium layers 51, and more preferably within 1.0 mm. In this way, as shown in Figures 2 and 6, the exposed portion 30 sandwiched between the winding core becomes the winding center 18, and an electrode body 3 with a wound structure in which the positive electrode 4 and the negative electrode 5 are wound in a spiral shape via the separator 6 can be obtained.
[0074] In describing the cylindrical lithium primary battery, Figures 1 to 6 were used as references. However, these drawings merely illustrate an example of the battery of the present invention, and the battery of the present invention is not limited to those shown in these drawings.
[0075] The cylindrical lithium primary battery of the present invention can be applied to various applications in which known cylindrical lithium primary batteries are used. [Examples]
[0076] The present invention will be described in detail below based on examples. However, the following examples are not intended to limit the present invention.
[0077] Example 1 <Fabrication of the positive electrode> First, the positive electrode mixture was prepared using the following procedure. A conductive additive with a BET specific surface area of 800 m² was used. 22.5 parts by mass of Ketjenblack "EC300J" (product name) at 1 / g and 93.5 parts by mass of manganese dioxide with an average particle size of 35 μm as a positive electrode active material were mixed dry for 5 minutes using a planetary mixer. Then, an amount of water equivalent to 20% (by mass) of the total solid content was added and mixed for another 5 minutes. Next, PTFE dispersion (Daikin Industries, Ltd. "D-1") was added in a proportion of 4 parts by mass of PTFE. Finally, water was added until the total solid content ratio reached 74% by mass, and mixed for another 5 minutes to obtain the positive electrode mixture.
[0078] Next, the positive electrode mixture was rolled into a sheet using a roll with a diameter of 250 mm and a temperature adjusted to 125 ± 5°C. A preliminary sheet was formed by drying it in a temperature environment of 105 ± 5°C until the residual moisture content was 2% by mass or less. Furthermore, the preliminary sheet was crushed using a pulverizer until it became a powder with a particle size of approximately 0.5 mm or less, and then rolled again using the aforementioned roll to obtain a sheet with a thickness of 0.7 mm and a density of 2.55 g / cm³. 3 This was used as the positive electrode mixture sheet. The manganese dioxide content per unit area in this positive electrode mixture sheet was 0.167 g / cm³. 2 That was the case.
[0079] The obtained positive electrode mixture sheet was cut to obtain an inner side positive electrode mixture sheet with a width of 37.5 mm and a length of 74 mm (positive electrode mixture sheet 41 in Figure 2) and an outer side positive electrode mixture sheet with a width of 37.5 mm and a length of 86 mm (positive electrode mixture sheet 42 in Figure 2).
[0080] Expanded metal made of stainless steel (SUS316) was used as the positive electrode current collector. This expanded metal was cut to a width of 35 mm and a length of 80 mm, and a stainless steel ribbon with a thickness of 0.1 mm and a width of 3 mm was attached to the center of the length direction as the positive electrode lead by resistance welding. Furthermore, carbon paste (manufactured by Nippon Graphite Co., Ltd.) was applied to this expanded metal so as not to crush the mesh, and then dried at a temperature of 105 ± 5°C to form the positive electrode current collector. The amount of carbon paste applied was 5 mg / cm³ after drying. 2I made it so that it would be like that.
[0081] Next, with a positive electrode current collector interposed between the inner and outer positive electrode mixture sheets, only one end in the longitudinal direction was fixed to integrate each positive electrode mixture sheet and positive electrode current collector. Specifically, the inner and outer positive electrode mixture sheets were aligned at one end in the longitudinal direction, and the end of the positive electrode current collector was set so that it did not protrude from the aforementioned end of the two positive electrode mixture sheets. In this state, the two positive electrode mixture sheets were pressed together 5 mm from the aforementioned end by pressing, thereby integrating each positive electrode mixture sheet and positive electrode current collector. After that, a sheet-like positive electrode with a thickness of 1.5 mm and a width of 37.5 mm was obtained by hot-air drying at 300 ± 10 °C for 15 minutes.
[0082] <Fabrication of the negative electrode> A copper foil (negative electrode current collector) measuring 38 mm in width, 200 mm in length, and 15 μm in thickness was used as the negative electrode current collector. On top of this, two metallic lithium foils measuring 37 mm in width, 114 mm in length, and 0.22 mm in thickness, and another metallic lithium foil measuring 37 mm in width, 72 mm in length, and 0.22 mm in thickness, were placed with a 9 mm gap in the longitudinal direction. Furthermore, a sheet-like negative electrode was constructed by layering two aluminum foils measuring 35 mm in width, 114 mm in length, and 9 μm in thickness, and another aluminum foil measuring 35 mm in width, 72 mm in length, and 9 μm in thickness, on top of the metallic lithium foils. The ratio of the area of the aluminum foil to the area of the metallic lithium foil was 95%, and the metallic lithium foil and aluminum foil were aligned at both ends in the longitudinal direction and at the ends in the width direction that would be the bottom side of the battery when inserted into the outer casing. Furthermore, a nickel negative electrode lead body with a width of 3 mm, a length of 20 mm, and a thickness of 0.1 mm was pre-pressed onto the metallic lithium foil.
[0083] In this sheet-like negative electrode, the lithium content in the lithium layer is 0.0117 g / cm³ per unit area. 2The total area of the lithium layer was 91% of the area of the negative electrode current collector, and the ratio of the total amount of aluminum to the total amount of lithium in the entire lithium layer, including the formed lithium-aluminum alloy, was 0.21 by mass.
[0084] <Electrode preparation> Two layers of microporous PE film (porosity: 48%, air permeability: 160 seconds / 100 mL), measuring 44 mm in width, 199 mm in length, and 16 μm in thickness, were used as a separator.
[0085] As shown in Figure 4, adhesive tape was attached to the copper foil between the two metallic lithium foils of the sheet-like negative electrode, and then the two overlapping PE microporous films were attached to the adhesive tape to obtain a laminate in which a separator was superimposed on the sheet-like negative electrode. Next, as shown in Figures 5 and 6, the portion of the laminate to which the adhesive tape was attached was sandwiched between two halves of a winding core (diameter: 2.8 mm), and the negative electrode was wound around it about once together with the separator. Then, the positive electrode was placed so that the fixed end of the positive electrode mixture sheet was on the winding core side and wound around, obtaining an electrode body with 2.7 turns. The electrode body has the structure shown in Figure 2, except that the number of turns is slightly different.
[0086] Furthermore, the distance between the folded-over point of the negative electrode formed by the winding core during winding and the inner circumference end of the metallic lithium foil facing the inner surface of the positive electrode was approximately 1 mm, and the distance between the inner circumference end of the metallic lithium foil facing the outer surface of the positive electrode and the center of the winding was approximately 5 mm. From the center of the winding toward the positive electrode mixture layer on the outer surface of the positive electrode, a portion of approximately 5 mm in width was formed on the negative electrode current collector where the lithium layer was not laminated. In addition, during winding, the separator was positioned so that one end in the width direction of the separator (the end placed on the upper side of the battery) protruded 1.5 mm from the end of the negative electrode (the end placed on the upper side of the battery), and the other end of the separator that protruded from the positive electrode was bent toward the positive electrode side so that the end face of the positive electrode was covered with the separator.
[0087] <Battery assembly> The assembly process for a cylindrical lithium primary battery will be explained with reference to Figure 1. A bottomed cylindrical outer casing 2, made of nickel-plated cold-rolled steel sheet (SPCD) with a side thickness of 0.25 mm, has an insulating plate 14 made of PP with a thickness of 0.2 mm inserted into the bottom 2a, and the electrode body 3 is inserted on top of it with the positive electrode lead body 15 facing upwards.
[0088] The negative electrode lead body 16 of the electrode body 3 was resistance-welded to the inner surface of the outer casing 2, and the positive electrode lead body 15 was resistance-welded to the lower surface of the terminal body 9 after the insulating plate 10 was inserted.
[0089] For the electrolyte, a non-aqueous solution was prepared by dissolving LiCF3SO3 at a concentration of approximately 0.5 mol / L in a mixed solvent of ethylene carbonate, propylene carbonate, and dimethoxyethane (by volume ratio of approximately 10:23:67), and further containing adiponitrile at a ratio of 3.0% by mass. 3.85 g of this solution was injected into the outer container 2. The injection was carried out in three stages, with the entire amount injected under reduced pressure in the final stage. The ratio (by mass ratio) of the total amount of electrolyte to the total amount of manganese dioxide in the positive electrode mixture layer was 0.384. After the electrolyte was injected, the lid plate 7 was fitted onto the upper opening of the outer container 2, and the opening of the outer container 2 was sealed by laser welding the inner circumference of the opening end of the outer container 2 to the outer circumference of the lid plate 7.
[0090] <Pre-discharge, aging> After sealing, the battery was pre-discharged for 30 seconds using a 1Ω resistor, stored at 70°C for 6 hours, and then subjected to a secondary pre-discharge for 1 minute using a constant 1Ω resistor to form a lithium-aluminum alloy on the separator side surface of the sheet-like negative electrode. The battery after pre-discharge was aged at room temperature for 7 days, and the open-circuit voltage was measured to confirm that a stable voltage was obtained, resulting in a cylindrical lithium primary battery with an outer diameter of 17.0 mm and a total height of 45 mm.
[0091] Comparative Example 1 A cylindrical lithium primary battery was obtained in the same manner as in Example 1, except that a non-aqueous solution (a solution without adiponitrile) was used as the electrolyte, which was obtained by dissolving LiCF3SO3 at a concentration of approximately 0.5 mol / L in a mixed solvent of ethylene carbonate, propylene carbonate, and dimethoxyethane (by volume ratio of approximately 10:23:67).
[0092] For the cylindrical lithium primary batteries of Example 1 and Comparative Example 1 after aging, the internal impedance (initial internal impedance) of the batteries was measured by applying a 1 kHz AC current. Then, a 47 kΩ fixed resistor was connected to the batteries, and they were stored for 84 days at 80°C and 90% relative humidity while undergoing constant resistance discharge. The change in the internal impedance of the batteries during this period was measured. The results are shown in Figure 7.
[0093] As shown in Figure 7, the battery of Example 1, which contained adiponitrile, a type of dinitrile, in the electrolyte, was able to suppress the increase in internal impedance during high-temperature storage compared to the battery of Comparative Example 1. [Explanation of symbols]
[0094] 1. Cylindrical lithium primary battery 2 outer cans 3. Electrode body with a wound structure 4 Positive electrode 5 negative electrode 6 Separators 7 Lid plate 8. Insulating packing 9 Terminals 10 Insulating board 11 Base section 12 Side wall 13 Gas outlet 14 Insulating board 15 Positive electrode lead body 16. Negative electrode lead body 18 Center of winding 30 Exposed portion of the negative electrode current collector 31 Adhesive tape 32 Laminate 33-winding core 33a Transverse groove of the winding core 41, 42 Positive electrode mixture sheet (positive electrode mixture layer) 43 Positive electrode current collector 51 Lithium layer 51a Lithium metallic foil 51b Aluminum foil 52 Negative electrode current collector 61, 62 Separators
Claims
1. A cylindrical lithium primary battery comprising an electrode body formed by spirally winding a positive electrode and a negative electrode with a separator in between, and an electrolyte, sealed inside an outer casing, The positive electrode comprises a positive electrode current collector and positive electrode mixture layers arranged on both sides of the positive electrode current collector, the latter containing manganese dioxide as the positive electrode active material. The manganese dioxide content per unit area of the positive electrode mixture layer is 0.155 to 0.185 g / cm² per side of the positive electrode current collector. 2 And, The negative electrode includes a negative electrode current collector and a lithium layer laminated on one side of the negative electrode current collector. The lithium layer has a lithium-aluminum alloy formed on the separator side surface. The ratio of the total amount of aluminum to the total amount of lithium in the entire lithium layer is 0.15 to 0.36 by mass. The aforementioned electrolyte is characterized by containing dinitrile, forming a cylindrical lithium primary battery.
2. The cylindrical lithium primary battery according to claim 1, wherein the number of turns of the positive electrode is 2.5 or more and 3.5 or less.
3. The cylindrical lithium primary battery according to claim 1, wherein the ratio of the total amount of the electrolyte to the total amount of manganese dioxide is 0.365 to 0.4 by mass ratio.
4. The cylindrical lithium primary battery according to claim 1, wherein the lithium layer is divided into two parts with the winding center in between, and faces one of the positive electrode mixture layers arranged on both sides of the positive electrode current collector.
5. The cylindrical lithium primary battery according to claim 1, wherein the dinitrile contains succinonitrile or adiponitrile.
6. The cylindrical lithium primary battery according to claim 1, wherein the dinitrile content in the electrolyte is 0.1 to 5% by mass.
Citation Information
Patent Citations
Nonaqueous electrolyte solution and lithium cell using the same
JP2004179146A
Cylindrical non-aqueous electrolyte primary battery
WO2020054662A1